Grain-boundary fluctuations in two-dimensional colloidal crystals. - Skinner, T; Aarts, D; Dullens, R (2010)
We study grain-boundary fluctuations in two-dimensional colloidal crystals in real space and time using video microscopy. The experimentally obtained static and dynamic correlation functions are very well described by expressions obtained using capillary wave theory. This directly leads to values for the interfacial stiffness and the interface mobility, the key parameters in curvature-driven grain-boundary migration. Furthermore, we show that the average grain-boundary position exhibits a one-dimensional random walk as recently suggested by computer simulations [Z. T. Trautt, M. Upmanyu, and A. Karma, Science 314, 632 (2006)]. The interface mobility determined from the mean-square displacement of the average grain-boundary position is in good agreement with values inferred from grain-boundary fluctuations.